2018
DOI: 10.4012/dmj.2017-136
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cuspal deflection and volumetric shrinkage of different bulk fill composites using non-contact phase microscopy and micro-computed tomography

Abstract: The understanding of cuspal deflection and volumetric shrinkage of resin composites is necessary to assess and improve the placement techniques of resin-based materials. The aim of this study was to investigate the cuspal deflection and its relationship with volumetric polymerization shrinkage of different bulk-fill resin composites. The investigation was conducted using non-contact phase microscopy and micro-computed tomography. Thirty custom-milled aluminum blocks were fabricated for microscopy analysis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…Nevertheless, a lower Young's modulus may allow stress dissipation during the polymerization process, thus reducing the stress in bigger increments. 10 , 25 , 26 , 32 , 33 …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a lower Young's modulus may allow stress dissipation during the polymerization process, thus reducing the stress in bigger increments. 10 , 25 , 26 , 32 , 33 …”
Section: Discussionmentioning
confidence: 99%
“…The volume change of the resin composite samples was evaluated using the µCT evaluation method. Several studies have confirmed the validity of using µCT to evaluate the volumetric change of resin composite materials (Yoshikawa,Sadr [64],Hirata, Clozza [14], Zeiger, Sun [6], Prager, Pierce [76]). In this study, three specimens from each group were used and submitted to evaluation before and after the environmental challenge.…”
Section: Microct Analysismentioning
confidence: 99%
“…Nevertheless, increasing the volume of increments is thought to increase the amount of polymerization shrinkage, leading to greater contraction stress. Therefore, there have been concerns regarding the development of gap formation at cavity walls with the bulk-fill technique, but several studies reported that bulk-fill RBCs did not give rise to post-operative problems, gap formation and cuspal deflection [5][6][7][8][9][10] . The manufacturers claim that bulk-fill RBCs exhibit lower polymerization shrinkage than conventional RBCs because of advanced filler technology or the addition of modulators that decrease the polymerization rate.…”
Section: Introductionmentioning
confidence: 99%